Early combination of pulmonary vasodilators prevents chronic kidney disease progression in connective tissue disease‐associated pulmonary hypertension. (9th October 2021) - Hanaoka, Hironari; Ishigaki, Sho; Takei, Hiroshi; Hiramoto, Kazuoto; Saito, Shuntaro; Kondo, Yasushi; Kikuchi, Jun; Kaneko, Yuko; Takeuchi, Tsutomu
Abstract: Aim: Pulmonary hypertension (PH) and chronic kidney disease (CKD) are interdependent for their development and exacerbation. We evaluated the effect of PH on CKD progression in patients with connective tissue disease (CTD)‐associated PH. Methods: We reviewed consecutive patients with CTD who were diagnosed with PH with right heart catheter (RHC) examinations in our hospital. Patients were divided into 2 groups according to the use of vasodilators: monotherapy or combination therapy. We further divided the patients with combination therapy into early and non‐early combination groups. Early combination was defined as the addition of the second vasodilator within 1 month after starting the first drug. The clinical course of hemodynamics and CKD progression were compared. Results: Thirty‐eight patients were included in the analysis: 10 were treated with monotherapy and 28 with combination therapy (14 with early and 14 with non‐early). At baseline, patients who received combination therapy had a significantly higher mean pulmonary arterial pressure with RHC and a higher right ventricular systolic pressure (RVSP) with echocardiography ( P  = .04) and showed a greater improvement in RVSP after treatment than those who underwent monotherapy. The incidence of CKD progression was significantly lower in patients who received combination therapy than in those who received monotherapy ( P  = .05). Among patients who received combination therapy, the early combination group had a lower incidence of CKD progression than the non‐early combination group ( P  = .03). Conclusions: Early combination therapy is associated with a lower incidence of CKD progression in patients with CTD‐associated PH.